Reducing Test Anxiety by Device-Guided Breathing: A Pilot Study - Ovadia-Blechman, Zehava; Tarrasch, Ricardo; Velicki, Maria; Chalutz Ben-Gal, Hila (Frontiers in Psychology, 2022)
Test anxiety remains a challenge for students and has considerable physiological and psychological impacts. The routine practice of slow, Device-Guided Breathing (DGB) is a major component of behavioral treatments for anxiety conditions. This paper addresses the effectiveness of using DGB as a self-treatment clinical tool for test anxiety reduction. This pilot study sample included 21 healthy men and women, all college students, between the ages of 20 and 30. Participants were randomly assigned to two groups: DGB practice (n = 10) and wait-list control (n = 11). At the beginning and the end of 3-weeks DGB training, participants underwent a stress test, followed by measures of blood pressure and reported anxiety. Anxiety reduction in the DGB group as compared to controls was not statistically significant, but showed a large effect size. Accordingly, the clinical outcomes suggested that daily practice of DGB may lead to reduced anxiety. We assume that such reduction may lead to improved test performance. Our results suggest an alternative treatment for test anxiety that may also be relevant for general anxiety, which is likely to increase due to the ongoing COVID-19 pandemic.